Legal Liability of Abortion Perpetrators of Rape Victims in Indonesia: Pertanggungjawaban Hukum Pelaku Aborsi Korban Pemerkosaan di Indonesia - Nini Ayu Nataria Rawis; Ahmad Riyadh UB; Emy Rosnawati (Academia Open, 2021)
Abortion is generally an act of abortion that is carried out without giving the opportunity to live outside the womb for certain reasons. Abortion committed by rape victims becomes a polemic in the context of criminal law to be held accountable. There are different formulations in the regulations that regulate even though these regulations regulate the same material so that rape victims who have abortions can be criminally charged. The method used is a statutory (normative) approach by using data collection namely laws and secondary sources of material in the form of previous thesis, books, scientific journals, and other literacy. The results of the research obtained are that the perpetrators of abortion victims of rape cannot be held criminally responsible because of the principle of no crime without fault where the perpetrators of abortion of rape victims have abortions which are prohibited by the Criminal Code but in accordance with the provisions of Article 75 paragraph (2) of Law Number 36 of 2009 concerning Health that allows abortion due to rape.